New Brighton, Port Elizabeth c1903-1953 : a history of an urban African community - Baines, Gary Fred (University of Cape Town, 2016)
Bibliography: pages 266-283. === This thesis explores the history of New Brighton in the context of Port Elizabeth's political economy. This port city was essentially an entrepôt until primary industrialisation commenced after the First World War. Jobs in the footwear and motor assembly plants were the preserve of unskilled white (Afrikaans-speaking) workers recently arrived from the city's hinterland. A relatively stable African population grew in the absence of influx controls, and provided a large pool of unskilled labour. A fairly large Coloured population made it more difficult for Africans to acquire employment and skills. With the spurt in industrial growth from the mid- 1940s, Africans were increasingly employed in the manufacturing sector. But the majority of the African workforce still performed unskilled work at or below the minimum wage. Port Elizabeth's African population was amongst the most fully proletarianised but the poorest in the country. The changing labour needs of Port Elizabeth's employers meant that the powerful commercial-cum- industrial lobby sought to influence the City Council to ignore influx control measures introduced in the 1930s. Instead, routine control of New Brighton residents was dependent on a 'location strategy' which included the issue of registration cards as the key to obtaining houses and beer brewing privileges. The Advisory Board provided a channel for patronage dispensed by the Superintendent and a means of co-opting prominent residents and their supporters. The usual litany of social ills such as grinding poverty, overcrowding and breakdown of family structures led to the growth of a subculture of violence amongst some of the youth from the late 1940s. This fed into the simmering discontent caused by the Council's insistence on rent increases and the heightened political expectations caused by the defiance campaign, which irrupted 'in the 1952 riots. Meanwhile, a realignment of political forces in the local state had changed the balance of power in favour of those groups which advocated a tighter rein on labour regulation and the political activities of local Africans. Pressure from this source and the central state in the aftermath of the riots, was more telling than that of the 'liberal' lobby and business interests on the PECC. The combination of state repression and the Council's hastily introduced curbs on political activities reduced the likelihood of ANC-led resistance to the imposition of passes. In 1953 the Council finally jettisoned its 'liberalism' and introduced influx control measures and labour registration. It applied the full force of the law against New Brighton residents whose reputation for being a law-abiding community had served to vindicate the Council's 'progressive' policies towards Africans in the first place.